Effects of proprotein convertase subtilisin kexin type 9 modulation in human pancreatic beta cells function. (June 2021) - Ramin-Mangata, Stéphane; Thedrez, Aurélie; Nativel, Brice; Diotel, Nicolas; Blanchard, Valentin; Wargny, Matthieu; Aguesse, Audrey; Billon-Crossouard, Stéphanie; Vindis, Cécile; Le May, Cédric; Hulin, Philippe; Armanet, Mathieu; et al.
Abstract: Background and aims: Proprotein Convertase Subtilisin Kexin Type 9 (PCSK9) is an endogenous inhibitor of the LDL receptor (LDLR). Mendelian randomization studies suggest that PCSK9 deficiency increases diabetes risk, but the underlying mechanisms remain unknown. The aim of our study was to investigate whether PCSK9 or its inhibition may modulate beta cell function. Methods: We assessed PCSK9 and insulin colocalization in human pancreatic sections by epifluorescent and confocal microscopy. We also investigated the expression and the function of PCSK9 in the human EndoC−βH1 beta cell line, by ELISA and flow cytometry, respectively. PCSK9 was inhibited with Alirocumab or siRNA. LDLR expression and LDL uptake were assessed by flow cytometry. Results: PCSK9 was expressed and secreted from beta cells isolated from human pancreas as well as from EndoC−βH1 cells. PCSK9 secretion was enhanced by statin treatment. Recombinant PCSK9 decreased LDLR abundance at the surface of these cells, an effect abrogated by Alirocumab. Alirocumab as well as PCSK9 silencing increased LDLR expression at the surface of EndoC−βH1 cells. Neither exogenous PCSK9, nor Alirocumab, nor PCSK9 silencing significantly altered glucose-stimulated insulin secretion (GSIS) from these cells. High-low density lipoproteins (LDL) concentrations decreased GSIS, but the addition of PCSK9 or its inhibition did not modulate this phenomenon. Conclusions: While PCSK9 regulates LDLR abundance in beta cells, inhibition of exogenous or endogenous PCSK9 does not appear to significantly impact insulin secretion. This is reassuring for the safety of PCSK9 inhibitors in terms of beta cell function. Graphical abstract: Image 1 Highlights: Like statins, PCSK9 inhibitors have been proposed to increase diabetes risk. Human pancreatic beta cells express and secrete PCSK9. The LDL receptor is regulated by exogenous and endogenous PCSK9 in beta cells. PCSK9 or its inhibition does not alter insulin secretion from human beta cells. Inhibiting circulating PCSK9 appears safe in terms of beta cell function and associated diabetes risk.